2016
DOI: 10.11604/pamj.2016.25.216.10247
|View full text |Cite
|
Sign up to set email alerts
|

Psychose aigüe secondaire à une dysthyroïdie: à propos de 2 cas

Abstract: Des anomalies fonctionnelles de la thyroïde sont fréquentes et touchent près de 5 % de la population générale, avec une prédominance pour les femmes. La survenue de troubles mentaux, en particulier de l'humeur, au cours des affections thyroïdiennes est connue depuis plus d'un siècle, alors que les troubles psychotiques associés aux dysthyroïdies sont rarement décrits. Nous rapportons les observations de 2 patientes présentant des troubles psychotiques dans deux situations différentes, la première suite à une h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
2
0
2
Order By: Relevance
“…Thyroidectomies with intrathoracic extent requiring neck dissection due to malignant neck nodes mostly involved central neck dissection of level VI (21% of patients), followed by neck node levels II, V, III and IV, which are draining sites of thyroid carcinoma neck node metastasis. This is consistent with the NCCN (2023) recommendation 18 that clinically positive and/or biopsy-proven nodal metastases be treated with formal compartmental resection in the central neck with unilateral or bilateral level VI dissection, and in the lateral compartment, a formal modified radical neck dissection including levels II, III, IV, and V.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thyroidectomies with intrathoracic extent requiring neck dissection due to malignant neck nodes mostly involved central neck dissection of level VI (21% of patients), followed by neck node levels II, V, III and IV, which are draining sites of thyroid carcinoma neck node metastasis. This is consistent with the NCCN (2023) recommendation 18 that clinically positive and/or biopsy-proven nodal metastases be treated with formal compartmental resection in the central neck with unilateral or bilateral level VI dissection, and in the lateral compartment, a formal modified radical neck dissection including levels II, III, IV, and V.…”
Section: Discussionsupporting
confidence: 87%
“…Patients experiencing post-operative delirium from thyroidectomy are rare, limited to case reports. 18,25 Other documented complications from local literature include postoperative hemorrhage, and respiratory failure. 7 The local study of Villaluna and Desales showed that the histopathologic results of intrathoracic goiters were mostly multinodular adenomatous goiters (50%) and follicular adenomas (7%) 7 .…”
Section: Discussionmentioning
confidence: 99%
“…But there is minimal literature available for the acute states of hypothyroidism following total thyroidectomy that would have led to psychosis. With best of our efforts, we could find only two case reports of psychosis in patients who underwent thyroidectomy, and only one in which patient developed psychosis in the immediate postoperative period [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…L'hypothyroïdie peut s'exprimer par un tableau dépressif associant un ralentissement du débit verbal, une diminution des performances intellectuelles, une fatigabilité, une diminution de l'appétit et une apathie. La « folie myxoedémateuse », décrite pour la première fois en 1949 [1], réalise un tableau d'état psychotique confusodélirant et hallucinatoire ou d'état mélancolique fréquemment stuporeux, plus rarement d'hypomanie [5]. Cette dernière forme est rarement observée et peu décrite dans la littérature, ce qui souligne l'originalité de notre observation.…”
Section: Discussionunclassified
“…Ces symptômes persistent bien souvent plus longtemps que les troubles somatiques [9]. Aussi, il est estimé dans la littérature que 10 % des patients présentent des symptômes neuropsychiatriques résiduels [5,13,14], justifiant alors une prescription d'antipsychotique au long cours.…”
Section: Discussionunclassified